2023
DOI: 10.3390/molecules28020730
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit Seed Extract-Added Functional Films and Coating for Active Packaging Applications: A Review

Abstract: Recently, consumers have been increasingly inclined towards natural antimicrobials and antioxidants in food processing and packaging. Several bioactive compounds have originated from natural sources, and among them, grapefruit seed extract (GSE) is widely accepted and generally safe to use in food. GSE is a very commonly used antimicrobial in food; lately, it has also been found very effective as a coating material or in edible packaging films. A lot of recent work reports the use of GSE in food packaging appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…The alginate‐ and carrageenan‐based films are commonly produced by employing a solution casting approach, and it has been reported that the neat films are brittle, and physical properties (mechanical, barrier, and hydrophobicity) are relatively weak for food packaging purposes (Roy & Rhim, 2020d; Santos et al., 2022a; Wang et al., 2023). Therefore, to enhance the physical and functional performances of both films, usually plasticizers, other polymers, cross‐linkers, and bioactive functional ingredients (nanofillers, plant extract, bioactive compounds, natural colorant, and EOs) are usually added into the film‐forming formulation (Bose et al., 2023; Fadiji et al., 2023; Ghosh et al., 2023; Kishore et al., 2023; Roy, Ezati, et al., 2023; Roy, Zhang, et al., 2023). The combination of other polymers and the addition of plasticizers and cross‐linkers are highly effective to improve the packaging films’ physical properties; on the flip side, the incorporation of functional additives helps to impart the antioxidant, antimicrobial activity into the film (Khan, Priyadarshi, et al., 2023; Shankar & Rhim, 2018; Tran et al., 2020; Zhang et al., 2022).…”
Section: Alginate and Carrageenanmentioning
confidence: 99%
“…The alginate‐ and carrageenan‐based films are commonly produced by employing a solution casting approach, and it has been reported that the neat films are brittle, and physical properties (mechanical, barrier, and hydrophobicity) are relatively weak for food packaging purposes (Roy & Rhim, 2020d; Santos et al., 2022a; Wang et al., 2023). Therefore, to enhance the physical and functional performances of both films, usually plasticizers, other polymers, cross‐linkers, and bioactive functional ingredients (nanofillers, plant extract, bioactive compounds, natural colorant, and EOs) are usually added into the film‐forming formulation (Bose et al., 2023; Fadiji et al., 2023; Ghosh et al., 2023; Kishore et al., 2023; Roy, Ezati, et al., 2023; Roy, Zhang, et al., 2023). The combination of other polymers and the addition of plasticizers and cross‐linkers are highly effective to improve the packaging films’ physical properties; on the flip side, the incorporation of functional additives helps to impart the antioxidant, antimicrobial activity into the film (Khan, Priyadarshi, et al., 2023; Shankar & Rhim, 2018; Tran et al., 2020; Zhang et al., 2022).…”
Section: Alginate and Carrageenanmentioning
confidence: 99%
“…In order to prevent the loss of goods, the packaging industry is intended to be transformed into one that is environmentally and socially conscious through the introduction of certain legislative requirements. According to SPA (an American organization, the Sustainable Packaging Coalition), packaging should be safe, effective, efficient, and cyclical [ 100 ]. Manufacturers are searching for novel solutions by developing creative biodegradable packaging materials or employing renewable raw materials in order to adapt the industry to the current requirements and changes.…”
Section: Sustainable Contribution To the Societymentioning
confidence: 99%
“…Due to GSE's functional properties, there has been a growing interest in using GSE in the food sector as an alternative to chemical treatments over the last decade. Several studies have investigated the efficacy and safety of GSE application on foods, whether directly, in combination with coating materials, or incorporated into edible films [29,51]. However, to our knowledge, none of these studies have evaluated the effectiveness of GSE in preventing P. eryngii yellowing.…”
Section: Introductionmentioning
confidence: 99%